Design of a Magnetic-Sensor Based on Fe3O4 Nanofluid Infiltration - A. Aobaid, Rowida; S. Hussain, Hind (Al-Nahrain Journal of Science, 2020)
A magnetic sensor, using a Hollow core-photonic crystal fiber infiltrated by a small amount of a magnetic nanofluid Fe3O4, is designed. The optical properties of this kind of fiber and the relation between the magnetic field and the magnetic nanofluid are employed to build the sensor. Laser light with the wavelength 674 nm is used to conduct the setup. A linear response in the wavelength-shift, of the transmitted spectrum corresponding to the applied magnetic field, is obtained. The wavelength-shift maintains its linearity throughout a range of magnetic field (0-245) Oe. The magnetic sensor shows a significant sensitivity about 19.03 m/Oe.